An Assessment of Parents' Book-sharing Quality, Children's Level of Engagement, and the Effects on Children's Verbal Exchanges - Kaleebu, Nasiib (Professional Communications Unit, 2024)
A process evaluation study was conducted for the Book-sharing for Families Programme, implemented by Living Hope in South Africa. Living Hope is a faith-based organisation that was established in the year 2000 with a vision of reaching people for Christ, bringing hope, and breaking the despair of poverty and disease. The Book-sharing for Families Programme aimsto strengthen capacity of parents and caregivers to foster positive relationships and provide enriching environment for their children that enable them grow and develop pre-literacy skills (including language development, concentration development, and book handling skills) that are needed for children to be ready to acquire reading when they go to school. The programme targets parents of low socioeconomic status and children aged 30 to 60 months, and it is implemented using a seven-week curriculum. The purpose of this evaluation was to examine the extent to which the programme achieved its short-term outcomes (effect on children's verbal exchange) and to gain a deeper understanding of how well the programme was implemented. Children's verbal exchange was assessed before and after the end of the programme using the Naturalistic Assessment of Verbal Exchanges tool, and the children's level of orientation to book-sharing was assessed using the Children Orientation to Booksharing (COB) rating scale. This was supplemented by data collected through interviews with the programme participants. Whereas the findings of the evaluation revealed that the programme did not have a statistically significant affect on children's verbal exchange, the programme had positive effects on the participants. The book-sharing interactions deepened children's orientation to shared reading, which according to the literature reviewed impacts on other child's development domains, including language and vocabulary acquisition. This study developed a logic model to guide the development and evaluation of similar programmes. The study introduced COB as a new tool which Living Hope had not previously used to supplement the existing tools and assist in examining the level of children's interest, engagement, and attention to book-sharing activities